2019
DOI: 10.1007/s10461-019-02720-4
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Sexual Risk Compensation Following PrEP Initiation Among Heterosexual HIV Serodiscordant Couples in Kenya and Uganda

Abstract: Recent studies among men who have sex with men suggest that sexual behaviors associated with risk of sexually transmitted infections increase following initiation of pre-exposure prophylaxis (PrEP) for HIV prevention. We used longitudinal data from HIV-uninfected participants (n = 1013) enrolled in an open-label study of PrEP delivered to Ugandan and Kenyan heterosexual HIV serodiscordant couples to understand the association between PrEP initiation and HIV risk-related sexual behaviors among these couples. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…In the Partners Demonstration Project, which tested this strategy of time-limited PrEP use among >1000 heterosexual serodiscordant couples in Kenya and Uganda, risk of HIV transmission was reduced by 96% in the context of condomless sex being reported by ∼40% of participants across follow-up. 4 , 5 These findings have supported country-level guidelines that recommend PrEP discontinuation once the partner living with HIV achieves sustained ART use. 6 , 7…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In the Partners Demonstration Project, which tested this strategy of time-limited PrEP use among >1000 heterosexual serodiscordant couples in Kenya and Uganda, risk of HIV transmission was reduced by 96% in the context of condomless sex being reported by ∼40% of participants across follow-up. 4 , 5 These findings have supported country-level guidelines that recommend PrEP discontinuation once the partner living with HIV achieves sustained ART use. 6 , 7…”
Section: Introductionmentioning
confidence: 74%
“… 22 25 By contrast, a recent longitudinal analysis of heterosexual HIV serodiscordant couples enrolled in the Partner Demonstration Project found no evidence of risk compensation, with total sex acts and condomless sex acts steadily decreasing over time after PrEP initiation. 5 We identified only one study that assessed changes in sexual risk after PrEP discontinuation. A secondary analysis of 1743 MSM and transgender women who participated in the iPrEX trial showed a 3.9% decrease in reported condomless receptive anal intercourse 8 weeks after PrEP discontinuation ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is mixed evidence to suggest that PrEP users engage in risk compensation. While Traeger et al's (2018) systematic review found that most open-label studies of PrEP use that reported sexual risk outcomes showed evidence of an increase in condomless sex among PrEP users (HIV-negative MSM and transgender women), there is evidence to suggest that PrEP does little to alter pre-existing behaviour (Hojilla et al 2016;Ortblad et al 2020) and participants' decision-making regarding safe sex practices appears to be influenced by various personal, psychosocial, and health-related factors, which PrEP does little to change (Hojilla et al 2016;Gafos et al 2019).…”
Section: The Impact Of Prep Coveragementioning
confidence: 99%
“…19,20 This might not apply generally, as no evidence of risk compensation following PrEP initiation was seen for heterosexual HIV serodiscordant couples in Kenya and Uganda. 21 Evidence from sub-Saharan African settings of risk compensation in response to rollout of voluntary medical male circumcision is also mixed, with two of three of the randomized clinical trials finding evidence of small increases in condom-related and sexual contact frequency risk behaviors, [22][23][24] but not with respect to number of partners, and recent evidence following rollout has not identified significant increases in risk behaviors among circumcised men. [25][26][27][28][29] An observational study in Kenya estimated that men undergoing voluntary medical circumcision were 42% more likely to report two or more sexual partners in the previous year.…”
Section: Introductionmentioning
confidence: 99%